Resolving Business Disputes Through Small Claims Court To Support The Ease Of Doing Business In Indonesia (Comparison: Netherlands And Malaysia) - Retnaningsih, Sonyendah; Suherman; Maskanah, Ummi; Sugiyono, Heru (International Journal of Psychosocial Rehabilitation, 2020)
In a business conflict, dispute resolution process that fast and provides legal certainty are necessity for justice seekers. The principle of justice that is fast, effective, efficient and low-cost is something that is highly expected in the process of settling a civil case in court. However, in reality, the dispute resolution procedure under the Civil Procedure Code in the court is still felt to be too long process, and the procedure is complicated and raises costs that are quite high. Therefore, addressing these conditions requires a Civil Procedure Law mechanism that can resolve a business dispute whose value is not too expensive with a simple and fast procedure. To overcome this problem, the Supreme Court Regulation No. 2 of 2015 concerning Simple Laws was issued as one of the mechanisms for resolving business disputes. This shows that basically the Supreme Court strongly support the process of resolving a case quickly, easily, cheaply and does not too long process. Law enforcement through the handling of business disputes in the Court that are fast, effective, efficient, light costs with a relatively short period of time become one of the indicators in creating a climate of easy going business in the business field in Indonesia. The problems that are to be examined are how to implement business dispute resolution through a small claim court in court in creating a climate of business convenience in the business field in Indonesia. This research in relation to the mechanism of settlement of disputes through small claim court was carried out in 2 (two) courts, the Denpasar Bali District Court, Depok District Court In addition, the research was also carried out by comparing of small claim court procedures in the Netherlands and Malaysia. The research method used in reviewing the legal issues examined is to use a normative juridical research method through library studies to obtain secondary data, as well as using a comparative approach.Keywords: